Ã¢â‚¬Å“SamenessÃ¢â‚¬Â as A Form of Hegemony to Create Utopian Society in Lois LowryÃ¢â‚¬â„¢s Ã¢â‚¬Å“The GiverÃ¢â‚¬Â - Zen, Umu Nisbatul Fauziah; Hetami, Fatma (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
Hegemony is defined as a condition under which a group establishes its supremacy not only by physical force but also through a consensual submission of the people who are dominated. This study aims to describe how Ã¢â‚¬Å“SamenessÃ¢â‚¬Â is represented as a form of hegemony to create utopian society in The Giver and to describe the kinds of hegemony found in the novel. The methodology used in this study was descriptive-qualitative. By using sociological approach, this study analyzed the novel from the point of view of hegemony, a theory developed by Antonio Gramsci. There were two objects of the study, namely material object which was The Giver novel and formal object taken from the analysis of the novel using theory of hegemony. The results of this study show that system of Ã¢â‚¬Å“SamenessÃ¢â‚¬Â is represented as a form of hegemony to create utopian society, seen from the episode of climate control which is created to avoid unpredictable weather, episode of family unit to control the populations of the community by regulating some procedures and rituals, episode of assignments by observing each of the citizensÃ¢â‚¬â„¢ interest through volunteer hours and recreation time, episode of precision of language and attitude to keep good communication and behavior; episode of no individual choices, episode of artificial sense which limit the vision, audio, and feeling after the removal of memory, and episode of punishments for rule breakers. There are three kinds of hegemony found in the novel based on the level of domination and resistance, namely Integral hegemony which is seen from the full obedience of the citizens towards the authority of the Committee of Elders, Decadent hegemony which is depicted by the citizensÃ¢â‚¬â„¢ disrespect and boredom towards the rules, and Minimal hegemony which happens due to the the resistance from the Receiver of Memory against the Committee of Elders despite the transformismo. Keywords: Sameness, Hegemony, Utopian society